1998
DOI: 10.1063/1.368075
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and coercivity of SmCo5 magnets

Abstract: The effects of alloy composition and heat treatment on the intrinsic coercivity Hci of SmCo5 magnets were studied. Alloys having six chemical compositions near that of stoichiometric SmCo5 were used to produce magnets via the usual powder metallurgy techniques. Magnets were either as sintered (1150 °C) or sintered (1150 °C) and treated at 850 °C. The substantial increase in Hci due to the 850 °C heat treatment occurs reversibly and with a negligible change in lattice parameters, Curie temperature Tc and anisot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 12 publications
3
12
0
Order By: Relevance
“…Therefore, the V of SmCo 5 continuously expands with the increase in Sm content, which verifies the existence of the high-temperature homogeneity range for SmCo 5 . A similar tendency of change of lattice parameters with the variation of Sm content was observed in sintered SmCo 5 magnets [16,17]. and Figure 3c summarizes the deduced magnetic properties.…”
Section: Experimental Methodssupporting
confidence: 53%
“…Therefore, the V of SmCo 5 continuously expands with the increase in Sm content, which verifies the existence of the high-temperature homogeneity range for SmCo 5 . A similar tendency of change of lattice parameters with the variation of Sm content was observed in sintered SmCo 5 magnets [16,17]. and Figure 3c summarizes the deduced magnetic properties.…”
Section: Experimental Methodssupporting
confidence: 53%
“…It has been suggested that the removal of lattice defects can be the responsible for the large increase of coercivity between sintering and heat treatment temperatures [2,3]. Even with a detailed verification of microstructure, before and after the post-sintering heat treatment in SmCo 5 [3,4,23] and NdFeB [4] magnets, no significant difference was found in microstructure, supporting the idea that the elimination of defects in atomic level can be the reason of the beneficial effect of heat treatment.…”
Section: Lattice Defects and Coercivitysupporting
confidence: 51%
“…Previous microstructural studies [3,4,23] indicated that a possible microstructural change-between sintering and heat-treatment temperatures-is the elimination of rare-earth atoms from a supersatured matrix. The calculation presented in this study will take into account the experimentally measured diffusion coefficients of Sm into SmCo 5 phase [24][25][26] and the Sm-Co phase diagram [27].…”
Section: Lattice Defects and Coercivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The inset also shows the temperature dependence of the coercive field, H C (T), which appears to have a dependence similar to the remanence. To conclude, we note that the observed 2.5 T coercive field is on the order of those found in some important rare-earth permanent magnets, such as Nd 2 Fe 14 B where  o H C ~ 2.6 T 20 , and SmCo 5 where  o H C ~ 4 T. 21 The large coercivity of nanostructured Mn x Ga films is also present in the electronic properties through the anomalous Hall effect (AHE). The Hall effect in magnetic materials contains two main contributions, ρ H (H) = R o H + R 1 M(H,T), where R o = -1/ne is the ordinary Hall effect (OHE) coefficient, n the carrier concentration, R 1 the AHE coefficient, and M(H,T) the field and temperature-dependent magnetization.…”
mentioning
confidence: 99%